Work-related socioeconomic determinants of health: evidence from educational mismatch in Italy - Abbafati, Cristiana; Rosano, Aldo (Frontiers in Public Health, 2024)
An educational mismatch is defined as the situation where the education qualifications of an employee do not match the qualifications required for the job they do. A mismatch can be vertical where the level of the employee's qualification is not the one required by the job. This study contributes to the literature on work-related social determinants of health, by carrying out the first assessment of the relationship between educational mismatch and health in Italy. Data come from PLUS, a national survey of labor supply. The risk of suffering from bad or very bad health associated with educational mismatch is investigated through a logistic regression model accounting for the socioeconomic context and occupation. Our findings show women are at greater risk of suffering from bad or very bad health than men, especially if under-educated. Our results show the need to address more research on work-related social determinants of health, which can represent a barrier to achieving health equity.